Punt in the 'Northern' Topographical Lists. Issue 1 (June 2018) - Cooper, Julien
Egyptian scribes presented their knowledge of foreign geography in an epigraphic corpus known as the Topographical Lists. These lists are an important and often under-utilized source for Egypt's foreign contacts in the Levant and Africa. As a list of placenames and sometimes also the names of tribes or peoples, they represent an Egyptian geographic encyclopaedia of peripheral regions as transcribed and understood by Egyptian scribes. Copied again and again over centuries, the list of names remain difficult to read, interpret, and map through the myriad copying difficulties and a lack of understanding of their original composition and precise purpose. This analysis addresses a philological and geographical enigma relating to the Levantine northern Topographical Lists, but is indicative of the many philological and geographical problems present in this corpus.